Genetik Algoritma ile Çok Kullanıcı Dfbç Sistemleri için Toplam Veri Hızı Enbüyüklemeli Uyarlanır Alttaşıyıcı ve Bit Yerleşimi - Özbek, Berna; Özbek, Berna; Le Ruyet, Didier (Institute of Electrical and Electronics Engineers Inc., 2008)
In this work, we perform the adaptive subcarrier and bit allocation to maximize the sum data rate for multiuser OFDM systems using genetic algorithm. Since the convergence time of the genetic algorithm could be slow, we propose to use a different initial condition to accelerate it without increasing the complexity of genetic algorithm and sacrificing the performance of the system. We obtain the simulation results and compare them with the classical methods. We show that the genetic algorithm with proposed initial condition gives better performances than the classical ones for sum data rate maximized allocation.
Sum-Rate Maximized Adaptive Subcarrier and Bit Allocation for Multiuser Ofdm Systems With Genetic Algorithm
IEEE 16th Signal Processing and Communications Applications Conference